Ceramic material with high thermal shock resistance and preparation method thereof
By introducing pretreated mullite fibers and mineralizers into the alumina ceramic material and using spray granulation and other processes, the problem of poor thermal shock properties of ceramic materials is solved, and higher thermal shock properties and more reliable MCH heating body properties are achieved.
Patent Information
- Application Number
- CN202411799560.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing alumina ceramic materials are prone to cracking when water cools to room temperature after heating, resulting in poor thermal shock, limiting their performance and service life.
Ceramic materials including alumina powder, pretreated mullite fibers, binders, dispersants and mineralizers are prepared by pretreatment of mullite fibers, mixing and stirring, spray granulation, molding and sintering.
It effectively improves the thermal shock properties of ceramic materials, so that they will not crack after being heated until the water is cooled to room temperature, and can withstand higher temperature changes, improving the performance and reliability of the MCH heating body.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic materials, and in particular to a high thermal shock ceramic material and a preparation method thereof. Background Art
[0002] Alumina ceramics are a type of aluminum oxide (Al 2 O 3 ) as the main ceramic material, due to its excellent physical and chemical properties, is widely used in many fields. 2 O 3 Different types of porcelain are classified into 99 porcelain, 95 porcelain, 90 porcelain, 85 porcelain, etc. The 99 alumina porcelain is used to make high-temperature crucibles, refractory furnace tubes and special wear-resistant materials; the 95 alumina porcelain is mainly used as corrosion-resistant and wear-resistant parts; the 85 porcelain is often mixed with talc to improve the electrical properties and mechanical strength, and can be sealed with metals such as molybdenum, niobium, and tantalum, and some are used as electric vacuum devices.
[0003] Alumina ceramics can be used in atmospheres up to 1650 degrees Celsius and in vacuum environments up to 2000 degrees Celsius. At 1000 degrees Celsius, it can still maintain 50% of its tensile strength at room temperature. This property makes it possible to use it in high-temperature environments, such as in the manufacture of spark plugs, high-temperature crucibles, refractory furnace tubes, etc.
[0004] Alumina ceramic materials are widely used in MCH heating elements, but ceramic materials have poor thermal shock resistance and are prone to cracking during the process of water cooling to room temperature after heating, which limits their performance and service life. Therefore, improving the thermal shock resistance of ceramic materials has become a key issue. Summary of the invention
[0005] In view of this, the present invention aims at the deficiencies in the prior art, and its main purpose is to provide a high thermal shock resistance ceramic material and a preparation method thereof, which can effectively solve the problem of poor thermal shock resistance of existing ceramic materials.
[0006] To achieve the above purpose, the present invention adopts the following technical solutions: A high thermal shock ceramic material comprises the following raw materials in parts by weight: 100 parts of alumina powder, 3-18 parts of pretreated mullite fibers, 2-8 parts of a binder, 2-5 parts of a dispersant and 2-8 parts of a mineralizer, wherein the mineralizer is composed of 1-4 parts of aluminum fluoride and 1-4 parts of magnesium fluoride.
[0007] As a preferred solution, the purity of the alumina powder is 99.5% and the average particle size is 2-4 μm.
[0008] As a preferred solution, the pretreated mullite fiber consists of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 30-50%, the purity is 98%, the diameter is 1-6 μm, and the length is 100-300 μm.
[0009] As a preferred solution, the binder is polyvinyl alcohol with a concentration of 5-10%.
[0010] As a preferred embodiment, the dispersant consists of 1-3 parts of polyacrylamide and 1-2 parts of polyethylene glycol.
[0011] A method for preparing a high thermal shock ceramic material comprises the following steps: (1) Mullite fiber pretreatment: soak the mullite fiber in phosphoric acid + zirconium oxychloride solution for 1-2 hours, then rinse with 50-60°C saturated calcium hydroxide + barium hydroxide solution, and then dry for use; (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a stirring device according to proportions and mix them thoroughly for later use; (3) Spray granulation: The mixed materials are subjected to spray granulation treatment for standby use; (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing; (5) Sintering: The ceramic body is sintered at 1550-1620°C to obtain a high thermal shock resistance ceramic material.
[0012] As a preferred solution, the phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution is 0.5-3%, and the zirconium oxychloride concentration is 2-10%.
[0013] As a preferred solution, during the spray granulation, the inlet temperature is controlled at 180-220°C, and the outlet temperature is controlled at 80-120°C.
[0014] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that: By pretreating the mullite fiber, a low expansion composite fiber component is formed at high temperature, and a mineralizer is introduced to stabilize the fiber strength and structure at high temperature. The alumina composite granulation powder is prepared by the spray granulation process. The mullite fiber forms a network structure in the ceramic material and has a smaller thermal expansion coefficient, which effectively absorbs thermal stress, so that the ceramic material does not crack when it is water-cooled to room temperature after heating, and can withstand higher temperature changes, effectively improving the thermal shock resistance of the ceramic material; at the same time, alumina powder as the main component ensures high hardness and high strength, and the addition of mullite fiber improves the toughness and impact resistance of the material. This product is suitable for MCH heating body, meets its high requirements for thermal shock resistance of ceramic materials, and improves the performance and reliability of MCH heating body. DETAILED DESCRIPTION
[0015] The invention discloses a high thermal shock ceramic material, comprising the following raw materials by weight: 100 parts of alumina powder, 3-18 parts of pretreated mullite fibers, 2-8 parts of a binder, 2-5 parts of a dispersant and 2-8 parts of a mineralizer, wherein the mineralizer is composed of 1-4 parts of aluminum fluoride and 1-4 parts of magnesium fluoride.
[0016] The alumina powder is used as the main component to provide high hardness and high temperature resistance of the ceramic material. The purity of the alumina powder is 99.5% and the average particle size is 2-4μm. The pretreated mullite fiber is composed of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 30-50%, the purity is 98%, the diameter is 1-6μm, and the length is 100-300μm. The mullite fiber is evenly dispersed in the alumina powder, which can effectively improve the thermal shock resistance of the ceramic material. The mullite fiber has excellent high temperature resistance, oxidation resistance, low thermal expansion coefficient and other properties, and forms a mesh structure in the ceramic material to enhance the toughness and thermal shock resistance of the material. The binder is polyvinyl alcohol or carboxymethyl cellulose, etc., with a concentration of 5-10%. The binder is used to bond the alumina powder and the mullite fiber together to form a stable composite granulation powder. The dispersant is composed of 1-3 parts of polyacrylamide and 1-2 parts of polyethylene glycol. The two dispersants are selected to promote the uniform dispersion of mullite fibers in alumina powder and improve the performance stability of the composite granulated powder.
[0017] The present invention also discloses a method for preparing the aforementioned high thermal shock ceramic material, comprising the following steps: (1) Mullite fiber pretreatment: The mullite fiber is soaked in phosphoric acid + zirconium oxychloride solution for activation for 1-2 hours, then rinsed with 50-60°C saturated calcium hydroxide + barium hydroxide solution, and then dried for use. The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution is 0.5-3%, and the zirconium oxychloride concentration is 2-10%. The phosphoric acid + zirconium oxychloride solution activates and disperses the fiber, promotes bonding with alumina ceramics, and during the high-temperature sintering process of the fiber, the residual solution on the surface will form a layer of negative expansion Ca1−x Ba x Zr 4 (PO 4 ) 6 Compounds reduce the overall expansion coefficient of the material and thus improve the thermal shock resistance of the material.
[0018] (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a mixing device in proportion and mix them thoroughly for later use. The stirring time and speed are adjusted according to the actual situation to ensure that all components are evenly mixed.
[0019] (3) Spray granulation: The mixed materials are subjected to spray granulation for standby use. Appropriate spray granulation parameters are set, such as inlet temperature, outlet temperature, atomization pressure, etc. During the spray granulation, the inlet temperature is controlled at 180-220°C, and the outlet temperature is controlled at 80-120°C.
[0020] (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing.
[0021] (5) Sintering: The ceramic body is sintered at 1550-1620°C to obtain a high thermal shock resistance ceramic material.
[0022] The present invention is further described in detail below with multiple embodiments and comparative examples: Embodiment 1: This embodiment discloses a high thermal shock ceramic material, including the following raw materials by weight: 100 parts of alumina powder, 3 parts of pretreated mullite fibers, 4 parts of a binder, 2 parts of a dispersant, and 3 parts of a mineralizer, wherein the mineralizer is composed of 1 part of aluminum fluoride and 2 parts of magnesium fluoride.
[0023] The purity of the alumina powder is 99.5%, and the average particle size is 3 μm. The pretreated mullite fiber is composed of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 35%, the purity is 98%, the diameter is 5 μm, and the length is 100 μm. The binder is polyvinyl alcohol with a concentration of 5%. The dispersant is composed of 1 part of polyacrylamide and 1 part of polyethylene glycol.
[0024] This embodiment also discloses a method for preparing the aforementioned high thermal shock ceramic material, comprising the following steps: (1) Pretreatment of mullite fiber: The mullite fiber was activated by soaking in phosphoric acid + zirconium oxychloride solution for 1.3 hours, then rinsed with 52°C saturated calcium hydroxide + barium hydroxide solution, and then dried for use. The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution was 0.8%, and the zirconium oxychloride concentration was 7%.
[0025] (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a mixing device in proportion and mix them thoroughly for later use. The stirring time and speed are adjusted according to the actual situation to ensure that all components are evenly mixed.
[0026] (3) Spray granulation: The mixed materials are subjected to spray granulation for standby use. Appropriate spray granulation parameters are set, such as inlet temperature, outlet temperature, atomization pressure, etc. During the spray granulation, the inlet temperature is controlled at 190°C and the outlet temperature is controlled at 120°C.
[0027] (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing.
[0028] (5) Sintering: The ceramic body is sintered at 1600°C to obtain a high thermal shock resistance ceramic material.
[0029] Embodiment 2: This embodiment discloses a high thermal shock ceramic material, including the following raw materials by weight: 100 parts of alumina powder, 15 parts of pretreated mullite fibers, 2 parts of a binder, 2.1 parts of a dispersant, and 5 parts of a mineralizer, wherein the mineralizer is composed of 2 parts of aluminum fluoride and 3 parts of magnesium fluoride.
[0030] The purity of the alumina powder is 99.5%, and the average particle size is 2 μm. The pretreated mullite fiber is composed of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 35%, the purity is 98%, the diameter is 2 μm, and the length is 150 μm. The binder is polyvinyl alcohol with a concentration of 9%. The dispersant is composed of 1 part of polyacrylamide and 1.1 parts of polyethylene glycol.
[0031] This embodiment also discloses a method for preparing the aforementioned high thermal shock ceramic material, comprising the following steps: (1) Pretreatment of mullite fiber: The mullite fiber was activated by soaking in phosphoric acid + zirconium oxychloride solution for 1.3 hours, then rinsed with 52°C saturated calcium hydroxide + barium hydroxide solution, and then dried for use. The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution was 1%, and the zirconium oxychloride concentration was 2%.
[0032] (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a mixing device in proportion and mix them thoroughly for later use. The stirring time and speed are adjusted according to the actual situation to ensure that all components are evenly mixed.
[0033] (3) Spray granulation: The mixed materials are subjected to spray granulation for standby use. Appropriate spray granulation parameters are set, such as inlet temperature, outlet temperature, atomization pressure, etc. During the spray granulation, the inlet temperature is controlled at 190°C and the outlet temperature is controlled at 120°C.
[0034] (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing.
[0035] (5) Sintering: The ceramic body is sintered at 1550°C to obtain a high thermal shock resistance ceramic material.
[0036] Embodiment 3: This embodiment discloses a high thermal shock ceramic material, comprising the following raw materials in parts by weight: 100 parts of alumina powder, 5 parts of pretreated mullite fibers, 7 parts of a binder, 3.6 parts of a dispersant, and 4 parts of a mineralizer, wherein the mineralizer is composed of 3 parts of aluminum fluoride and 1 part of magnesium fluoride.
[0037] The purity of the alumina powder is 99.5%, and the average particle size is 2.5 μm. The pretreated mullite fiber is composed of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 35%, the purity is 98%, the diameter is 3 μm, and the length is 250 μm. The binder is polyvinyl alcohol with a concentration of 7%. The dispersant is composed of 2 parts of polyacrylamide and 1.6 parts of polyethylene glycol.
[0038] This embodiment also discloses a method for preparing the aforementioned high thermal shock ceramic material, comprising the following steps: (1) Pretreatment of mullite fiber: The mullite fiber was activated by soaking in phosphoric acid + zirconium oxychloride solution for 1.3 hours, then rinsed with 52°C saturated calcium hydroxide + barium hydroxide solution, and then dried for use. The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution was 3%, and the zirconium oxychloride concentration was 5%.
[0039] (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a mixing device in proportion and mix them thoroughly for later use. The stirring time and speed are adjusted according to the actual situation to ensure that all components are evenly mixed.
[0040] (3) Spray granulation: The mixed materials are subjected to spray granulation for standby use. Appropriate spray granulation parameters are set, such as inlet temperature, outlet temperature, atomization pressure, etc. During the spray granulation, the inlet temperature is controlled at 190°C and the outlet temperature is controlled at 120°C.
[0041] (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing.
[0042] (5) Sintering: The ceramic body is sintered at 1610°C to obtain a high thermal shock resistance ceramic material.
[0043] Embodiment 4: This embodiment discloses a high thermal shock ceramic material, comprising the following raw materials in parts by weight: 100 parts of alumina powder, 10 parts of pretreated mullite fibers, 8 parts of a binder, 5 parts of a dispersant, and 2 parts of a mineralizer, wherein the mineralizer is composed of 1 part of aluminum fluoride and 1 part of magnesium fluoride.
[0044] The purity of the alumina powder is 99.5%, and the average particle size is 3.5 μm. The pretreated mullite fiber is composed of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 35%, the purity is 98%, the diameter is 6 μm, and the length is 200 μm. The binder is polyvinyl alcohol with a concentration of 6%. The dispersant is composed of 3 parts of polyacrylamide and 2 parts of polyethylene glycol.
[0045] This embodiment also discloses a method for preparing the aforementioned high thermal shock ceramic material, comprising the following steps: (1) Pretreatment of mullite fiber: The mullite fiber was activated by soaking in phosphoric acid + zirconium oxychloride solution for 1.3 hours, then rinsed with 52°C saturated calcium hydroxide + barium hydroxide solution, and then dried for use. The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution was 2%, and the zirconium oxychloride concentration was 9%.
[0046] (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a mixing device in proportion and mix them thoroughly for later use. The stirring time and speed are adjusted according to the actual situation to ensure that all components are evenly mixed.
[0047] (3) Spray granulation: The mixed materials are subjected to spray granulation for standby use. Appropriate spray granulation parameters are set, such as inlet temperature, outlet temperature, atomization pressure, etc. During the spray granulation, the inlet temperature is controlled at 190°C and the outlet temperature is controlled at 120°C.
[0048] (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing.
[0049] (5) Sintering: The ceramic body is sintered at 1620°C to obtain a high thermal shock resistance ceramic material.
[0050] Embodiment 5: This embodiment discloses a high thermal shock ceramic material, comprising the following raw materials in parts by weight: 100 parts of alumina powder, 18 parts of pretreated mullite fibers, 5 parts of a binder, 3 parts of a dispersant, and 7 parts of a mineralizer, wherein the mineralizer is composed of 3 parts of aluminum fluoride and 4 parts of magnesium fluoride.
[0051] The purity of the alumina powder is 99.5%, and the average particle size is 4 μm. The pretreated mullite fiber is composed of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 35%, the purity is 98%, the diameter is 4 μm, and the length is 300 μm. The binder is polyvinyl alcohol with a concentration of 8%. The dispersant is composed of 1.5 parts of polyacrylamide and 1.5 parts of polyethylene glycol.
[0052] This embodiment also discloses a method for preparing the aforementioned high thermal shock ceramic material, comprising the following steps: (1) Pretreatment of mullite fiber: The mullite fiber was activated by soaking in phosphoric acid + zirconium oxychloride solution for 1.3 hours, then rinsed with 52°C saturated calcium hydroxide + barium hydroxide solution, and then dried for use. The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution was 0.5%, and the zirconium oxychloride concentration was 10%.
[0053] (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a mixing device in proportion and mix them thoroughly for later use. The stirring time and speed are adjusted according to the actual situation to ensure that all components are evenly mixed.
[0054] (3) Spray granulation: The mixed materials are subjected to spray granulation for standby use. Appropriate spray granulation parameters are set, such as inlet temperature, outlet temperature, atomization pressure, etc. During the spray granulation, the inlet temperature is controlled at 190°C and the outlet temperature is controlled at 120°C.
[0055] (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing.
[0056] (5) Sintering: The ceramic body is sintered at 1580°C to obtain a high thermal shock resistance ceramic material.
[0057] Embodiment 6: This embodiment discloses a high thermal shock ceramic material, comprising the following raw materials in parts by weight: 100 parts of alumina powder, 8 parts of pretreated mullite fibers, 6 parts of a binder, 3.8 parts of a dispersant, and 8 parts of a mineralizer, wherein the mineralizer is composed of 4 parts of aluminum fluoride and 4 parts of magnesium fluoride.
[0058] The purity of the alumina powder is 99.5%, and the average particle size is 3 μm. The pretreated mullite fiber is composed of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 35%, the purity is 98%, the diameter is 1 μm, and the length is 180 μm. The binder is polyvinyl alcohol with a concentration of 10%. The dispersant is composed of 2.5 parts of polyacrylamide and 1.3 parts of polyethylene glycol.
[0059] This embodiment also discloses a method for preparing the aforementioned high thermal shock ceramic material, comprising the following steps: (1) Pretreatment of mullite fiber: The mullite fiber was activated by soaking in phosphoric acid + zirconium oxychloride solution for 1.3 hours, then rinsed with 52°C saturated calcium hydroxide + barium hydroxide solution, and then dried for use. The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution was 2.5%, and the zirconium oxychloride concentration was 8%.
[0060] (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a mixing device in proportion and mix them thoroughly for later use. The stirring time and speed are adjusted according to the actual situation to ensure that all components are evenly mixed.
[0061] (3) Spray granulation: The mixed materials are subjected to spray granulation for standby use. Appropriate spray granulation parameters are set, such as inlet temperature, outlet temperature, atomization pressure, etc. During the spray granulation, the inlet temperature is controlled at 190°C and the outlet temperature is controlled at 120°C.
[0062] (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing.
[0063] (5) Sintering: The ceramic body is sintered at 1590°C to obtain a high thermal shock resistance ceramic material.
[0064] Comparative Example 1: The difference between the comparative example and the above-mentioned embodiment 4 is that the conventional 95 alumina ceramic is used in the comparative example. The rest of the contents of the comparative example are the same as those of the embodiment 4 and will not be described again here.
[0065] Comparative Example 2: The difference between the comparative example and the above-mentioned embodiment 4 is that the mullite fiber pretreatment method is not used in this comparative example. The rest of the contents of this comparative example are the same as those of embodiment 4 and will not be repeated here.
[0066] Comparative Example 3: The difference between the comparative example and the above-mentioned embodiment 4 is that no mineralizer is added in this comparative example. The rest of the contents of this comparative example are the same as those of embodiment 4 and will not be repeated here.
[0067] The strength test of the ceramic materials obtained in the above embodiments and comparative examples is carried out below. The strength test method is usually a conventional strength test method. The strength test results are shown in the following table:
[0068] As can be seen from the above table, from Examples 1, 2, 3 and 4 and Comparative Example 1, it can be seen that the traditional 95 alumina ceramic has low strength, severe strength loss under air cooling, and will crack after being heated to 210-220°C and rapidly water-cooled, affecting the use temperature range and safety of the MCH heater. From Examples 1, 2, 3 and 4 and Comparative Example 2, it can be seen that the maximum thermal shock temperature of the final ceramic heater can be increased by special treatment of the mullite fiber. The fiber rinsing process increases the dispersibility of the fiber, and the residual material re-forms a low expansion component at high temperature. From Examples 1, 2, 4 and 5 and Comparative Example 3, it can be seen that by adding mineralizers in proportion, the maximum thermal shock temperature of the final ceramic heater can be increased. During the high-temperature sintering process, the mineralizer promotes the further generation of mullite fibers and stabilizes the mullite fiber structure.
[0069] Compared with the traditional 95 alumina ceramics, the present invention has significant advantages: the traditional 95 alumina ceramics will crack after being heated to 210-220℃ and rapidly cooled by water, which affects the use temperature range and safety of the MCH heating body. However, after adding mullite fiber, the ceramic material of the present invention can be rapidly cooled by water at 260-250℃ without cracking, and the thermal shock resistance is greatly improved. The design focus of the present invention is: by pretreating mullite fiber, a low-expansion composite fiber component is formed at high temperature, and a mineralizer is introduced to stabilize the fiber strength and structure at high temperature, and alumina composite granulation powder is prepared by a spray granulation process. Mullite fiber forms a network structure in the ceramic material and has a smaller thermal expansion coefficient, effectively absorbing thermal stress, so that the ceramic material does not crack when it is water-cooled to room temperature after heating, and can withstand higher temperature changes, effectively improving the thermal shock resistance of the ceramic material; at the same time, alumina powder as the main component ensures high hardness and high strength, and the addition of mullite fiber improves the toughness and impact resistance of the material. This product is suitable for MCH heating body, meets its high requirements for the thermal shock resistance of ceramic materials, and improves the performance and reliability of the MCH heating body.
[0070] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high thermal shock resistance ceramic material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of alumina powder, 3-18 parts of pretreated mullite fibers, 2-8 parts of a binder, 2-5 parts of a dispersant and 2-8 parts of a mineralizer, wherein the mineralizer is composed of 1-4 parts of aluminum fluoride and 1-4 parts of magnesium fluoride.
2. The high thermal shock resistance ceramic material according to claim 1, characterized in that: The aluminum oxide powder has a purity of 99.5% and an average particle size of 2-4 μm.
3. The high thermal shock resistance ceramic material according to claim 1, characterized in that: The pretreated mullite fiber consists of mullite fiber and alumina fiber, wherein the mass content of the mullite fiber is 30-50%, the purity is 98%, the diameter is 1-6 μm, and the length is 100-300 μm.
4. The high thermal shock resistance ceramic material according to claim 1, characterized in that: The binder is polyvinyl alcohol with a concentration of 5-10%.
5. The high thermal shock resistance ceramic material according to claim 1, characterized in that: The dispersant consists of 1-3 parts of polyacrylamide and 1-2 parts of polyethylene glycol.
6. A method for preparing a high thermal shock ceramic material according to any one of claims 1 to 5, characterized in that: The following steps are included: (1) Mullite fiber pretreatment: soak the mullite fiber in phosphoric acid + zirconium oxychloride solution for 1-2 hours, then rinse with 50-60°C saturated calcium hydroxide + barium hydroxide solution, and then dry for use; (2) Mixing and stirring: Add alumina powder, pretreated mullite fiber, binder, dispersant and mineralizer into a stirring device according to proportions and mix them thoroughly for later use; (3) Spray granulation: The mixed materials are subjected to spray granulation treatment for standby use; (4) Molding: The powder obtained by the spray granulation is formed into a ceramic body of a desired shape by dry pressing or isostatic pressing; (5) Sintering: The ceramic body is sintered at 1550-1620°C to obtain a high thermal shock resistance ceramic material.
7. The method for preparing a high thermal shock ceramic material according to claim 6, characterized in that: The phosphoric acid concentration in the phosphoric acid + zirconium oxychloride solution is 0.5-3%, and the zirconium oxychloride concentration is 2-10%.
8. The method for preparing a high thermal shock ceramic material according to claim 6, characterized in that: During the spray granulation, the inlet temperature is controlled at 180-220°C, and the outlet temperature is controlled at 80-120°C.
Citation Information
Patent Citations
Thermal shock and creep resistant porous mullite articles prepared from topaz and process for manufacture
CA2048441A1
Novel fiber toughened alumina ceramic and preparation method thereof
CN115180968A
Sintered phosphate salt
JP1997268053A
Ceramic treating process and product produced thereby
US3817781A